Factors Influencing Impulsive Buying Behavior of Consumers: Evidence from Bhatbhateni Superstore - Dongol, Padam; Prajapati, Saroj (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This study examines the factors influencing impulsive buying behavior among consumers at Bhatbhateni Superstore. Impulse buying, defined as spontaneous and unplanned purchases, has gained significant attention due to its impact on consumer behavior and retail strategies. The study identifies various internal and external factors, such as store atmosphere, browsing behavior, layout, promotions, time availability, and money availability, that contribute to impulsive buying tendencies. A quantitative research approach, utilizing a descriptive design, was adopted, with data collected from 140 consumers through a structured questionnaire. The results revealed significant positive relationships between impulsive buying behavior and all the factors under investigation. Among these, in-store browsing showed the strongest correlation with impulsive buying. The findings support the rejection of all null hypotheses, indicating that each factor significantly influences impulsive buying behavior. These insights are valuable for retailers in designing store environments and promotional strategies aimed at enhancing impulse purchases. The study contributes to the understanding of impulsive buying behavior, particularly within the context of a superstore setting in Nepal.